High-temperature-resistant ultra-wear-resistant lightweight sole material and preparation method thereof
By using natural rubber, modified high styrene and composite staple fiber in sole materials, combined with specific processing and modification technologies, the problem of reduced flexibility after the introduction of high styrene is solved, and the resistance of sole materials is improved Abrasiveness, antibacteriality and wear comfort achieve high temperature and ultra-wear-resistant lightweight sole materials.
Patent Information
- Application Number
- CN202411320112.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-17
AI Technical Summary
After the introduction of high styrene rubber, existing sole materials have reduced flexibility and rebound performance, which affects wear comfort and is difficult to solve this problem while maintaining other excellent performances.
It uses natural rubber, modified high styrene, hollow glass microbeads, coupling agents, zinc carbonate, stearic acid, microcrystalline paraffin, active agents, anti-aging agents, accelerators and polydimethylsiloxanes. Prepare high temperature resistant ultra-wear-resistant lightweight sole materials through specific mixing and processing steps, including the preparation of modified high styrene and electrospinning technology of composite staple fibers, combining bonding reaction of coupling agents and microwave radiation to form antibacterial properties .
It improves the flexibility, elastic recovery, antibacteriality, wear resistance and mechanical properties of the sole material, enhances the resistance to high temperature and aging fatigue resistance, and improves the overall wear comfort and service life.
Smart Images

Figure BDA0005053608730000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sole materials, and in particular to a high-temperature resistant, super-wear-resistant and lightweight sole material and a preparation method thereof. Background Art
[0002] With the development of society and the improvement of people's living standards, consumers' demand for shoes is no longer limited to single functionality, but is developing towards diversification and personalization. When buying shoes, consumers pay more and more attention to the appearance design (fashion), wearing experience (comfort) and overall quality of the product (quality). These factors together constitute the core considerations of modern consumers when buying shoes.
[0003] As one of the important components of shoes, soles directly affect the service life, wearing experience and safety of shoes. Therefore, the research and development of sole materials has always been the focus of technological innovation in the footwear industry. In recent years, in order to meet consumers' higher requirements for sole functionality and quality, researchers have been committed to developing new materials and new processes that are more suitable for shoemaking needs.
[0004] For example, Chinese invention patent CN118240305A describes a lightweight composite material and its preparation method. This technology uses a mixture of polypropylene (PP), acrylonitrile-butadiene-styrene copolymer (ABS) and polyolefin elastomer (POE) as the main components, and introduces modified calcium aluminate as a reinforcing material, supplemented with an appropriate amount of additives, and through a series of processing steps such as granulation and injection molding, a good material with light weight, high strength, high toughness and wear resistance is produced.
[0005] However, although the above technical solution has improved the physical properties of the sole material to a certain extent, it was found in the actual application process that high styrene rubber, as a special type of styrene-butadiene rubber, can significantly improve the hardness, mechanical strength, tear resistance, wear resistance and folding resistance of the mixed rubber, and can effectively reduce the Mooney viscosity of high-hardness rubber, thereby improving the processing performance of the rubber, but its use also brings new challenges. Specifically, the addition of high styrene rubber significantly affects the original softness and elasticity of natural rubber, resulting in poor performance of the final sole material in terms of flexibility and rebound performance, thereby affecting the wearing comfort of the sole material.
[0006] In view of this, how to maintain or improve other excellent properties of the sole material while overcoming the problem of reduced flexibility and rebound performance caused by the introduction of high styrene rubber has become a technical problem that needs to be solved urgently.
[0007] Therefore, it is necessary to prepare a high temperature resistant, ultra-wear resistant and lightweight sole material to solve the above problems. Summary of the invention
[0008] In order to solve the existing technical problems, the present invention provides a high-temperature resistant, super-wear-resistant and lightweight sole material. The raw material components include, by weight: 85-105 parts of natural rubber, 15-22 parts of modified high styrene, 3-8 parts of hollow glass microspheres, 1-1.5 parts of coupling agent, 2-3 parts of zinc carbonate, 1-3 parts of stearic acid, 10-16 parts of microcrystalline wax, 8-12 parts of activator, 1.5-6 parts of antioxidant, 3-8 parts of accelerator and 20-35 parts of polydimethylsiloxane.
[0009] Furthermore, the modified high styrene rubber is obtained by mixing composite short fibers and high styrene rubber, adding a mixture of chlorosulfonated polyethylene and modified silicon nitride, and continuing to knead.
[0010] Furthermore, the modified silicon nitride is salicylaldehyde-modified silicon nitride.
[0011] Furthermore, the composite short fibers are obtained by two-component electrospinning and cutting of the rubber modifier SPE-100 and TPU using an eccentric nozzle.
[0012] Furthermore, the coupling agent is a mixture of silane coupling agent KH550 and an unsaturated silane coupling agent; the unsaturated silane coupling agent includes any one of vinyl trichlorosilane, 3-methacryloxypropyl trimethoxysilane, and bis-(3-triethoxysilylpropyl)-tetrasulfide.
[0013] On the one hand, the coupling agent can form bonds with highly dispersed hollow glass microspheres, and on the other hand, it can bond with rubber, so that it produces excellent static and dynamic physical properties after vulcanization, and the product performance is more stable; at the same time, the amino group in the coupling agent reacts with the aldehyde group in the modified high styrene under microwave radiation to form a Schiff base derivative, which makes the high temperature resistant, ultra-wear-resistant and lightweight sole material antibacterial.
[0014] Furthermore, the antioxidant is composed of styrenated phenol, 2-mercaptobenzimidazole and 2,2,4-trimethyl-1,2-dihydroquinoline in a weight ratio of 0.8-1.2:0.8-1.2:1.6-2.8.
[0015] Furthermore, the active agent is preferably polyethylene glycol.
[0016] Furthermore, the accelerator is preferably 2,2'-dibenzothiazole disulfide.
[0017] The present invention also provides a method for preparing a high temperature resistant, ultra-wear resistant and lightweight sole material, comprising the following steps:
[0018] (1) Add 85-105 parts by weight of natural rubber and 15-22 parts by weight of modified high styrene to an internal mixer, and mix for 50-70 seconds;
[0019] (2) adding 3 to 8 parts by weight of hollow glass microspheres to the internal mixer of step (1) and continuing to mix for 50 to 70 seconds;
[0020] (3) Add 1-1.5 parts by weight of coupling agent, 2-3 parts by weight of zinc carbonate, 1-3 parts by weight of stearic acid, 10-16 parts by weight of microcrystalline wax, 8-12 parts by weight of active agent, 1.5-6 parts by weight of antioxidant, 3-8 parts by weight of accelerator, and 20-35 parts by weight of polydimethylsiloxane to the internal mixer of step (2); when heated to 80-100° C., sweep, turn over, and hammer three times each, and keep the temperature constant for 3-6 minutes; when the temperature rises to 120-130° C., guide out the mass, treat it under 500 W microwave for 5 minutes, and then roll it into a 5 mm thick sheet through a double-roll calender, cool the sheet through water, dry it, and leave it for at least 24 hours to obtain a high temperature resistant, ultra-wear resistant, and lightweight sole material.
[0021] Furthermore, the specific steps of modifying high styrene in step (1) are as follows:
[0022] S1. Add the composite short fiber and high styrene rubber in a weight ratio of 1:2 to 3 into an internal mixer and mix for 3 to 5 minutes, raise the temperature to 90 to 110°C, and keep the temperature for 2 to 3 minutes to extract the mass;
[0023] S2. The chlorosulfonated polyethylene and the modified silicon nitride are mixed uniformly in a weight ratio of 1:1 to 3;
[0024] S3. Add the mass of step S1 and the product of step S2 into an internal mixer in a weight ratio of 16-23:2-3, heat to 90°C, keep the temperature constant for 3-6 minutes, and then heat to 100-110°C to extract the mixture to obtain modified high styrene.
[0025] Further, the preparation method of the composite short fiber is as follows: dissolving TPU in DMF to prepare a 12wt% TPU spinning solution; dissolving the rubber modifier SPE-100 in tetrahydrofuran to prepare a 22% SPE-100 spinning solution; using the SPE-100 spinning solution as the core layer and the TPU spinning solution as the shell layer, respectively putting them into two injection pumps for extrusion, and converging at the outlet of the eccentric nozzle, and being subjected to the high voltage applied by the high-voltage electrostatic generator, the fibers are formed and then fall on the drum, and then cut into short fibers with a length of 0.2 to 0.4 mm, wherein the high-voltage electrostatic voltage is 25KV, the distance from the nozzle head to the receiving drum is 15cm, the flow rate ratio of the SPE-100 spinning solution and the TPU spinning solution is 1:1, the solution extrusion speed is 0.6mL / h, and the drum speed is 40r / min; the air temperature is 20 (±2) ° C, and the relative humidity is 50% to 60%; wherein, TPU is formed by bonding The block copolymer formed by alternating crystalline hard segments and amorphous soft segments has good elasticity and flexibility. When subjected to stress, the hard segments distributed in the matrix composed of soft segments will play a skeleton role and disperse into the entire system to provide a fulcrum space for the soft segments so that the TPU segments can move. Therefore, TPU has excellent flexibility and elastic recovery performance. The composite fiber prepared by adding TPU and rubber modifier SPE100 to modified high styrene can improve the flexibility and elastic recovery of the sole material, and the rigidity of the rubber modifier SPE100 is much greater than that of TPU. When the two materials are eccentrically spun, an interfacial interaction is formed between the two. After being subjected to a certain stress, asymmetric contraction will be formed in the axial direction of the fiber, thereby forming a spiral structure. Then, the composite fiber prepared by adding TPU and rubber modifier SPE100 to modified high styrene can further enhance the flexibility and elastic recovery of the sole material.
[0026] Furthermore, the preparation method of the modified silicon nitride is as follows: nano silicon nitride and salicylaldehyde are added to acetone which is 50 times the mass of nano silicon nitride in a mass ratio of 1:0.04-0.06, and a high shear dispersing emulsifier is used to shear for 5 minutes at 2000 rpm, followed by constant temperature stirring at 30°C for 7.8-8.2 hours, and heating to volatilize and remove acetone to obtain modified silicon nitride.
[0027] Furthermore, the weight ratio of the silane coupling agent KH550 to the unsaturated silane coupling agent in the coupling agent is 0.5:0.5-1.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The present invention adopts natural rubber, modified high styrene, hollow glass microspheres, coupling agent, zinc carbonate, stearic acid, microcrystalline wax, activator, antioxidant, accelerator, and polydimethylsiloxane to prepare a high-temperature resistant, ultra-wear-resistant, lightweight sole material. The prepared high-temperature resistant, ultra-wear-resistant, lightweight sole material has good flexibility, elastic recovery, antibacterial property, wear resistance, and mechanical properties.
[0030] (2) The high-temperature resistant, ultra-wear-resistant and lightweight sole material of the present invention introduces modified high styrene. High styrene itself has excellent heat resistance and compatibility. The addition of composite short fibers can greatly improve its wear resistance. At the same time, the auxiliary agent silicon nitride itself has good wear resistance and good resistance to cold and hot shocks. The chlorosulfonyl group in the chlorosulfonated polyethylene is easily physically bonded with the active group on the surface of the modified silicon nitride, which can not only greatly improve the stability of the high styrene material in a high temperature environment, but also further improve the overall wear resistance.
[0031] (3) The composite short fiber of the present invention is obtained by two-component electrospinning and cutting of rubber modifier SPE-100 and TPU using an eccentric nozzle; wherein TPU is a block copolymer formed by alternating crystalline hard segments and amorphous soft segments, which has good elasticity and flexibility. When subjected to stress, the hard segments distributed in the matrix composed of soft segments will play a skeleton role and be dispersed throughout the system to provide a fulcrum space for the soft segments, so that the TPU segments can move. Therefore, TPU has excellent flexibility and elastic recovery performance. The composite fiber prepared by adding TPU and rubber modifier SPE100 to modified high styrene It can improve the flexibility and elastic recovery of the sole material, and the rigidity of the rubber modifier SPE100 is much greater than that of TPU. When the two materials are eccentrically spun, an interfacial interaction is formed between the two. After being subjected to a certain stress, asymmetric contraction will be formed in the axial direction of the fiber, thus forming a spiral structure. The composite fiber prepared by adding TPU and rubber modifier SPE100 to modified high styrene can further enhance the flexibility and elastic recovery of the sole material; the addition of rubber modifier SPE100 can enhance the wear resistance, flexibility, tear resistance and aging fatigue resistance of high-temperature resistant, ultra-wear-resistant and lightweight sole materials.
[0032] (4) The use of salicylaldehyde to modify nano-silicon nitride can effectively improve the dispersion performance of nano-silicon carbide in modified high styrene, thereby ensuring the mechanical properties of the sole material.
[0033] (5) Hollow glass microspheres have the advantages of light weight, low thermal conductivity, non-toxicity, non-flammability, good chemical stability and high dispersion. When used as fillers in the present invention, they can greatly reduce the basis weight of the finished product and further improve the wear resistance of the material.
[0034] (6) The coupling agent of the present invention adopts a mixture of silane coupling agent KH550 and unsaturated silane coupling agent; the coupling agent can form a bond with highly dispersed hollow glass microspheres on the one hand, and bond with rubber on the other hand, so that it produces excellent static and dynamic physical properties after vulcanization, and the product performance is also more stable; at the same time, the amino group in the coupling agent reacts with the aldehyde group in the modified high styrene under microwave radiation to form a Schiff base derivative, so that the high temperature resistant, ultra-wear resistant and lightweight sole material has antibacterial properties.
[0035] (7) The high temperature resistant, ultra-wear resistant and lightweight sole material of the present invention adopts polydimethylsiloxane, which can effectively improve the insulation and shockproof properties of the whole material. At the same time, polydimethylsiloxane itself is a dustproof oil, which can reduce the subsequent manual cleaning and improve efficiency. DETAILED DESCRIPTION
[0036] The present invention is further described in detail below in conjunction with examples, but the following examples should not be construed as limiting the present invention.
[0037] The raw materials for the examples and comparative examples of this application are as follows:
[0038] TPU uses Desmopan DP 2590A from Bayer, Germany;
[0039] Rubber modifier SPE-100 was obtained from Qingdao Siwei Chemical Co., Ltd.
[0040] Example 1
[0041] A method for preparing a high temperature resistant, ultra-wear resistant and lightweight sole material comprises the following steps:
[0042] (1) Add 85 parts by weight of natural rubber and 15 parts by weight of modified high styrene to an internal mixer and mix for 50 seconds;
[0043] (2) adding 3 parts by weight of hollow glass microspheres to the internal mixer of step (1) and continuing to mix for 50 seconds;
[0044] (3) Add 1 part by mass of coupling agent, 2 parts by mass of zinc carbonate, 1 part by mass of stearic acid, 10 parts by mass of microcrystalline wax, 8 parts by mass of active agent, 1.5 parts by mass of antioxidant, 3 parts by mass of accelerator and 20 parts by mass of polydimethylsiloxane to the internal mixer of step (2); when heated to 80°C, sweep, turn over and hammer three times respectively, and keep the temperature constant for 3 minutes; when the temperature rises to 120°C, extract the mass, treat it under 500W microwave for 5 minutes, and then roll it into a 5mm thick sheet by a double-roll calender, cool the sheet by water, dry it and leave it for at least 24 hours to obtain a high temperature resistant, ultra-wear resistant and lightweight sole material.
[0045] The specific steps of modifying high styrene in step (1) are as follows:
[0046] S1. The composite short fiber and high styrene rubber were added to an internal mixer in a ratio of 1:2 parts by weight and mixed for 3 minutes, and the temperature was raised to 90°C and kept at a constant temperature for 2 minutes to extract the mass;
[0047] S2. The chlorosulfonated polyethylene and the modified silicon nitride are mixed uniformly in a weight ratio of 1:1;
[0048] S3. Add the mass obtained by step S1 and the product obtained by mixing S2 into an internal mixer in a weight ratio of 16:2, heat to 90°C, keep the temperature constant for 3 minutes, and then heat to 100°C to extract the mixture to obtain modified high styrene.
[0049] The preparation method of the composite short fiber is as follows: TPU is dissolved in DMF to prepare a 12wt% TPU spinning solution; a rubber modifier SPE-100 is dissolved in tetrahydrofuran to prepare a 22% SPE-100 spinning solution; the SPE-100 spinning solution is used as a core layer and the TPU spinning solution is used as a shell layer, respectively, and the two are put into two injection pumps for extrusion, and converge at the outlet of an eccentric nozzle, and are jointly subjected to a high voltage applied by a high-voltage electrostatic generator, and then fall on a roller after being formed into fibers, and then cut into short fibers with a length of 0.2mm, wherein the high-voltage electrostatic voltage is 25KV, the distance from the nozzle head to the receiving roller is 15cm, the flow rate ratio of the SPE-100 spinning solution to the TPU spinning solution is 1:1, the solution extrusion speed is 0.6mL / h, and the roller speed is 40r / min; the air temperature is 20(±2)℃, and the relative humidity is 50%-60%.
[0050] The preparation method of the modified silicon nitride is as follows: nano silicon nitride and salicylaldehyde are added into acetone with a mass ratio of 1:0.04, and sheared at 2000 rpm for 5 minutes using a high shear dispersing emulsifier, followed by constant temperature stirring at 30° C. for 7.8 hours, and heated to volatilize and remove acetone to obtain modified silicon nitride.
[0051] The weight ratio of the silane coupling agent KH550 to the unsaturated silane coupling agent in the coupling agent is 0.5:0.5.
[0052] Example 2
[0053] A method for preparing a high temperature resistant, ultra-wear resistant and lightweight sole material comprises the following steps:
[0054] (1) Add 95 parts by weight of natural rubber and 19 parts by weight of modified high styrene to an internal mixer and mix for 60 seconds;
[0055] (2) adding 6 parts by weight of hollow glass microspheres to the internal mixer of step (1) and continuing to mix for 60 seconds;
[0056] (3) 1.3 parts by weight of coupling agent, 2.5 parts by weight of zinc carbonate, 2 parts by weight of stearic acid, 13 parts by weight of microcrystalline wax, 10 parts by weight of active agent, 4 parts by weight of antioxidant, 6 parts by weight of accelerator and 28 parts by weight of polydimethylsiloxane are successively added to the internal mixer of step (2); when heated to 90° C., the material is swept, turned and hammered three times each, and the constant temperature time is 5 min; when the temperature rises to 125° C., the mass is discharged, treated under a 500 W microwave for 5 min, and then rolled into a 5 mm thick sheet by a double-roll calender, the sheet is cooled by water, dried and placed for at least 24 h to obtain a high temperature resistant, ultra-wear resistant and lightweight sole material.
[0057] The specific steps of modifying high styrene in step (1) are as follows:
[0058] S1. The composite short fiber and high styrene rubber were added to an internal mixer in a weight ratio of 1:2.5 and mixed for 4 minutes, and the temperature was raised to 100°C and kept at a constant temperature for 2.5 minutes to extract the mass;
[0059] S2. The chlorosulfonated polyethylene and the modified silicon nitride are mixed uniformly in a weight ratio of 1:2;
[0060] S3. Add the mass obtained by step S1 and the product obtained by mixing S2 into an internal mixer in a weight ratio of 19:2.5, heat to 90°C, keep the temperature constant for 5 minutes, and then heat to 105°C to extract the mixture to obtain modified high styrene.
[0061] The preparation method of the composite short fiber is as follows: TPU is dissolved in DMF to prepare a 12wt% TPU spinning solution; a rubber modifier SPE-100 is dissolved in tetrahydrofuran to prepare a 22% SPE-100 spinning solution; the SPE-100 spinning solution is used as a core layer and the TPU spinning solution is used as a shell layer, respectively, and the two are put into two injection pumps for extrusion, and the two are merged at the outlet of an eccentric nozzle, and are jointly subjected to a high voltage applied by a high-voltage electrostatic generator, and then fall on a roller after being formed into fibers, and then cut into short fibers with a length of 0.3mm, wherein the high-voltage electrostatic voltage is 25KV, the distance from the nozzle head to the receiving roller is 15cm, the flow rate ratio of the SPE-100 spinning solution to the TPU spinning solution is 1:1, the solution extrusion speed is 0.6mL / h, and the roller speed is 40r / min; the air temperature is 20(±2)℃, and the relative humidity is 50%-60%.
[0062] The preparation method of the modified silicon nitride is as follows: adding nano silicon nitride and salicylaldehyde in a mass ratio of 1:0.05 to acetone which is 50 times the mass of the nano silicon nitride, using a high shear dispersing emulsifier to shear for 5 minutes at 2000 rpm, then stirring at a constant temperature of 30° C. for 8 hours, and heating to volatilize and remove the acetone to obtain the modified silicon nitride.
[0063] The weight ratio of the silane coupling agent KH550 to the unsaturated silane coupling agent in the coupling agent is 0.5:0.8.
[0064] Example 3
[0065] A method for preparing a high temperature resistant, ultra-wear resistant and lightweight sole material comprises the following steps:
[0066] (1) Add 105 parts by weight of natural rubber and 22 parts by weight of modified high styrene to an internal mixer and mix for 70 seconds;
[0067] (2) adding 8 parts by weight of hollow glass microspheres to the internal mixer of step (1) and continuing to mix for 70 seconds;
[0068] (3) Add 1.5 parts by weight of coupling agent, 3 parts by weight of zinc carbonate, 3 parts by weight of stearic acid, 16 parts by weight of microcrystalline wax, 12 parts by weight of active agent, 6 parts by weight of antioxidant, 8 parts by weight of accelerator and 35 parts by weight of polydimethylsiloxane to the internal mixer of step (2); when heated to 100° C., sweep, turn and hammer three times respectively, and keep the temperature constant for 6 minutes; when the temperature rises to 130° C., extract the mass, treat it under 500 W microwave for 5 minutes, and then roll it into a 5 mm thick sheet through a double-roll calender, cool the sheet through water, dry it and leave it for at least 24 hours to obtain a high temperature resistant, ultra-wear resistant and lightweight sole material.
[0069] The specific steps of modifying high styrene in step (1) are as follows:
[0070] S1. The composite short fiber and high styrene rubber were added to an internal mixer in a weight ratio of 1:3 and mixed for 5 minutes, and the temperature was raised to 110°C and the mass was extracted at a constant temperature for 3 minutes;
[0071] S2. The chlorosulfonated polyethylene and the modified silicon nitride are mixed uniformly in a weight ratio of 1:3;
[0072] S3. Add the mass obtained by step S1 and the product obtained by mixing S2 into an internal mixer in a weight ratio of 23:3, heat to 90°C, keep the temperature constant for 6 minutes, and then heat to 110°C to extract the mixture to obtain modified high styrene.
[0073] The preparation method of the composite short fiber is as follows: TPU is dissolved in DMF to prepare a 12wt% TPU spinning solution; a rubber modifier SPE-100 is dissolved in tetrahydrofuran to prepare a 22% SPE-100 spinning solution; the SPE-100 spinning solution is used as a core layer and the TPU spinning solution is used as a shell layer, respectively, and the two are put into two injection pumps for extrusion, and the two are merged at the outlet of an eccentric nozzle, and are subjected to a high voltage applied by a high-voltage electrostatic generator to form fibers, and then fall on a roller, and then are cut into short fibers with a length of 0.4mm, wherein the high-voltage electrostatic voltage is 25KV, the distance from the nozzle head to the receiving roller is 15cm, the flow rate ratio of the SPE-100 spinning solution to the TPU spinning solution is 1:1, the solution extrusion speed is 0.6mL / h, and the roller speed is 40r / min; the air temperature is 20(±2)℃, and the relative humidity is 50%-60%.
[0074] The preparation method of the modified silicon nitride is as follows: adding nano silicon nitride and salicylaldehyde in a mass ratio of 1:0.06 to acetone which is 50 times the mass of the nano silicon nitride, using a high shear dispersing emulsifier to shear for 5 minutes at 2000 rpm, then stirring at a constant temperature of 30° C. for 8.2 hours, and heating to volatilize and remove the acetone to obtain the modified silicon nitride.
[0075] The weight ratio of the silane coupling agent KH550 to the unsaturated silane coupling agent in the coupling agent is 0.5:1.
[0076] Comparative Example 1
[0077] The only difference between Comparative Example 1 and Example 2 is that the modified high styrene is obtained by mixing the fiber prepared by rubber modifier SPE-100 and high styrene rubber, adding the mixture of chlorosulfonated polyethylene and modified silicon nitride and continuing to knead, and the other ingredients and steps are the same as Example 2.
[0078] Comparative Example 2
[0079] The difference between Comparative Example 2 and Example 2 is that the modified high styrene is obtained by mixing the fiber prepared from TPU and high styrene rubber, adding the mixture of chlorosulfonated polyethylene and modified silicon nitride and continuing to knead. The other ingredients and steps are the same as those in Example 2.
[0080] Comparative Example 3
[0081] The only difference between Comparative Example 3 and Example 2 is that the modified high styrene is obtained by mixing the composite short fiber and high styrene rubber, adding the mixture of chlorosulfonated polyethylene and silicon nitride and continuing to knead; the other ingredients and steps are the same as those of Example 2.
[0082] Comparative Example 4
[0083] The only difference between Comparative Example 4 and Example 2 is that natural rubber, high styrene, hollow glass microspheres, coupling agent, zinc carbonate, stearic acid, microcrystalline wax, activator, antioxidant, accelerator, and polydimethylsiloxane are used to prepare high-temperature resistant, ultra-wear-resistant and lightweight sole materials, and the remaining ingredients and steps are the same as those in Example 2.
[0084] Comparative Example 5
[0085] The only difference between Comparative Example 5 and Example 2 is that natural rubber, high styrene, composite short fiber, chlorosulfonated polyethylene, modified silicon nitride, hollow glass microspheres, coupling agent, zinc carbonate, stearic acid, microcrystalline wax, activator, antioxidant, accelerator, and polydimethylsiloxane are used to prepare high temperature resistant, ultra-wear resistant and lightweight sole materials, and the remaining ingredients and steps are the same as those in Example 2.
[0086] Effect example
[0087] Antibacterial property: Taking Escherichia coli ATCC8099 as an example, the antibacterial rate is the maximum percentage of inhibiting and killing bacteria under certain antibacterial agent content and experimental conditions; at a temperature of 37°C, the oil-resistant antistatic sole materials prepared in the embodiments and comparative examples were placed in a special plastic bag, corresponding to 10 cm 2 Add 2 mL of inoculated bacterial solution to the sample sole, introduce air equivalent to the amount of inoculated bacterial solution into the plastic bag, heat seal the plastic bag, and oscillate at 37±1℃ for 24 hours. Determine the number of surviving bacteria by dilution plate culture method and calculate the antibacterial rate.
[0088] Wear resistance: The oil-resistant and antistatic sole materials prepared in the examples and comparative examples were tested for wear resistance according to GB / T1689-2014.
[0089] Elasticity: The deformation rate of the oil-resistant and antistatic sole materials prepared in the examples and comparative examples was tested according to GB / T1681.
[0090] Density: The oil-resistant and antistatic sole materials prepared in the examples and comparative examples were tested for density according to GB / T1.1-2009.
[0091] Tensile properties: The oil-resistant and antistatic sole materials prepared in the examples and comparative examples were tested for tensile strength according to GB / T528-2009.
[0092] Comfort: The oil-resistant and antistatic sole materials prepared in the examples and comparative examples can be made into high-temperature resistant, ultra-wear-resistant and lightweight soles through an injection molding machine. Wear the shoes made of the soles and walk 1 km to feel the comfort of the shoes.
[0093] Table 1 below shows the test results of various properties of the oil-resistant and antistatic sole materials prepared by using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0094] Table 1
[0095]
[0096] It can be found from Table 1 that the oil-resistant and antistatic sole material prepared in the embodiment is light in weight; elastic recovery, antibacterial property, wear resistance and mechanical properties are good; by comparing Examples 1 to 3 with Comparative Examples 1 to 3, it is found that after the composite short fiber and high styrene rubber are mixed, a mixture of chlorosulfonated polyethylene and modified silicon nitride is added and continued to be kneaded to obtain modified high styrene, and the oil-resistant and antistatic sole material prepared is light in weight; elastic recovery, antibacterial property, wear resistance and mechanical properties are good; by comparing Examples 1 to 3 with Comparative Examples 4 to 5, it is found that the high temperature resistant and ultra-wear resistant lightweight sole material is prepared by using modified high styrene, and the elastic recovery and mechanical properties of the obtained oil-resistant and antistatic sole material are good.
[0097] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
Claims
1. A high temperature resistant, ultra-wear resistant and lightweight sole material, characterized in that: The raw material components include, by weight: 85-105 parts of natural rubber, 15-22 parts of modified high styrene, 3-8 parts of hollow glass microspheres, 1-1.5 parts of coupling agent, 2-3 parts of zinc carbonate, 1-3 parts of stearic acid, 10-16 parts of microcrystalline wax, 8-12 parts of activator, 1.5-6 parts of antioxidant, 3-8 parts of accelerator and 20-35 parts of polydimethylsiloxane.
2. The high temperature resistant, ultra-wear resistant and lightweight sole material according to claim 1, characterized in that: The modified high styrene is obtained by mixing composite short fibers and high styrene rubber, adding a mixture of chlorosulfonated polyethylene and modified silicon nitride and continuing to knead.
3. The high temperature resistant, ultra-wear resistant and lightweight sole material according to claim 2, characterized in that: The modified silicon nitride is salicylaldehyde modified silicon nitride.
4. The high temperature resistant, ultra-wear resistant and lightweight sole material according to claim 2, characterized in that: The composite short fibers are obtained by performing two-component electrostatic spinning and cutting of a rubber modifier SPE-100 and TPU using an eccentric core nozzle.
5. The high temperature resistant, ultra-wear resistant and lightweight sole material according to claim 1, characterized in that: The coupling agent is a mixture of silane coupling agent KH550 and an unsaturated silane coupling agent.
6. A method for preparing the high temperature resistant, ultra-wear resistant and lightweight sole material according to any one of claims 1 to 5, characterized in that: The steps include: (1) Add 85-105 parts by weight of natural rubber and 15-22 parts by weight of modified high styrene to an internal mixer, and mix for 50-70 seconds; (2) adding 3 to 8 parts by weight of hollow glass microspheres to the internal mixer of step (1) and continuing to mix for 50 to 70 seconds; (3) 1-1.5 parts by weight of coupling agent, 2-3 parts by weight of zinc carbonate, 1-3 parts by weight of stearic acid, 10-16 parts by weight of microcrystalline wax, 8-12 parts by weight of active agent, 1.5-6 parts by weight of antioxidant, 3-8 parts by weight of accelerator, and 20-35 parts by weight of polydimethylsiloxane are continuously added to the internal mixer of step (2); when heated to 80-100° C., the mixture is cleaned, turned over, and hammered three times each, and the temperature is kept constant for 3-6 minutes; when the temperature rises to 120-130° C., the mass is discharged, treated at 500 W microwave for 5 minutes, and then rolled into a 5 mm thick sheet by a double-roll calender, the sheet is cooled by water, and left to stand for at least 24 hours after drying, to obtain a high temperature resistant, ultra-wear resistant, and lightweight sole material.
7. The method for preparing the high temperature resistant, ultra wear resistant and lightweight sole material according to claim 6, characterized in that: The specific steps of modifying high styrene in step (1) are as follows: S1. Add the composite short fiber and high styrene rubber in a weight ratio of 1:2 to 3 into an internal mixer and mix for 3 to 5 minutes, raise the temperature to 90 to 110°C, and keep the temperature for 2 to 3 minutes to extract the mass; S2. The chlorosulfonated polyethylene and the modified silicon nitride are mixed uniformly in a weight ratio of 1:1 to 3; S3. Add the mass of step S1 and the product of step S2 into an internal mixer in a weight ratio of 16-23:2-3, heat to 90°C, keep the temperature constant for 3-6 minutes, and then heat to 100-110°C to extract the mixture to obtain modified high styrene.
8. The method for preparing the high temperature resistant, ultra wear resistant and lightweight sole material according to claim 7, characterized in that: The preparation method of the composite short fiber is as follows: TPU is dissolved in DMF to prepare a 12wt% TPU spinning solution; a rubber modifier SPE-100 is dissolved in tetrahydrofuran to prepare a 22% SPE-100 spinning solution; the SPE-100 spinning solution is used as a core layer and the TPU spinning solution is used as a shell layer, respectively put into two injection pumps for extrusion, and merged at the outlet of an eccentric nozzle, and are jointly subjected to the high voltage applied by a high-voltage electrostatic generator, and then fall on a roller after being formed, and then cut into short fibers with a length of 0.2-0.4mm, wherein the high-voltage electrostatic voltage is 25KV, the distance from the nozzle head to the receiving roller is 15cm, the flow rate ratio of the SPE-100 spinning solution to the TPU spinning solution is 1:1, the solution extrusion speed is 0.6mL / h, and the roller speed is 40r / min; the air temperature is 20(±2)℃, and the relative humidity is 50%-60%.
9. The method for preparing the high temperature resistant, ultra wear resistant and lightweight sole material according to claim 7, characterized in that: The preparation method of the modified silicon nitride is as follows: adding nano silicon nitride and salicylaldehyde in a mass ratio of 1:0.04-0.06 to acetone which is 50 times the mass of the nano silicon nitride, using a high shear dispersing emulsifier to shear for 5 minutes at 2000 rpm, then stirring at a constant temperature of 30°C for 7.8-8.2 hours, and heating to volatilize and remove the acetone to obtain the modified silicon nitride.
10. The method for preparing the high temperature resistant, ultra wear resistant and lightweight sole material according to claim 9, characterized in that: The weight ratio of the silane coupling agent KH550 to the unsaturated silane coupling agent in the coupling agent is 0.5:0.5-1.
Citation Information
Patent Citations
Lightweight composite material and preparation method thereof
CN118240305A